2020
DOI: 10.3748/wjg.v26.i40.6224
|View full text |Cite
|
Sign up to set email alerts
|

New strain of Pediococcus pentosaceus alleviates ethanol-induced liver injury by modulating the gut microbiota and short-chain fatty acid metabolism

Abstract: BACKGROUND Intestinal dysbiosis has been shown to be associated with the pathogenesis of alcoholic liver disease (ALD), which includes changes in the microbiota composition and bacterial overgrowth, but an effective microbe-based therapy is lacking. Pediococcus pentosaceus ( P. pentosaceus ) CGMCC 7049 is a newly isolated strain of probiotic that has been shown to be resistant to ethanol and bile salts. However, further studies are needed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
(60 reference statements)
2
34
2
Order By: Relevance
“…Additionally, butyrate can restrain cytokine (TNFα and MCP-1) production following acute alcohol exposure, although it does not appear to ameliorate alcohol-induced steatosis [ 267 ]. Indirect benefits of SCFA supplementation might also be achieved through administration of Pediococcus pentosaceus , which increased the levels of the SCFAs possibly due to the partial recovery of bacterial genera, such as Clostridium, whose levels were decreased in the mouse model of chronic plus binge alcohol exposure and whose recovery could increase SCFA production, as suggested by the positive correlation found between Clostridium and butyric acid levels in this study [ 268 ]. Administration of other SCFAs or other beneficial microbial products may yield similar results to butyrate supplementation, such as administration of indole-3-propionic acid (IPA), an indole metabolite generated by the metabolism of tryptophan, which elevated gut tight junction proteins, thus preventing intestinal barrier dysfunction and liver damage in rats exposed to a Western-style HFD, possibly by the gut–liver axis [ 269 ].…”
Section: Translational Approaches and Therapeutics Against Alcoholmentioning
confidence: 94%
“…Additionally, butyrate can restrain cytokine (TNFα and MCP-1) production following acute alcohol exposure, although it does not appear to ameliorate alcohol-induced steatosis [ 267 ]. Indirect benefits of SCFA supplementation might also be achieved through administration of Pediococcus pentosaceus , which increased the levels of the SCFAs possibly due to the partial recovery of bacterial genera, such as Clostridium, whose levels were decreased in the mouse model of chronic plus binge alcohol exposure and whose recovery could increase SCFA production, as suggested by the positive correlation found between Clostridium and butyric acid levels in this study [ 268 ]. Administration of other SCFAs or other beneficial microbial products may yield similar results to butyrate supplementation, such as administration of indole-3-propionic acid (IPA), an indole metabolite generated by the metabolism of tryptophan, which elevated gut tight junction proteins, thus preventing intestinal barrier dysfunction and liver damage in rats exposed to a Western-style HFD, possibly by the gut–liver axis [ 269 ].…”
Section: Translational Approaches and Therapeutics Against Alcoholmentioning
confidence: 94%
“…Analysis of the faecal metabolome in humans with alcohol use disorders revealed a reduction in SCFAs, which is likely to be due in part to dysbiosis that negatively affects SCFA-producing bacteria such as Faecalibacterium [ 15 , 21 ]. Several murine models have reliably shown that supplementation with SCFAs in either the form of a high fibre diet, probiotic or dietary modification enhances gut epithelial integrity and reduces liver injury in alcoholic models, and work in this area is ongoing [ 22 , 23 , 24 ].…”
Section: Alcohol and The Gutmentioning
confidence: 99%
“…Meanwhile, there have been reports on the intervention of the gut microbiota in acute alcoholic liver disease. The supplementation of Pediococcus pentosaceus CGMCC 7,049 improved the intestinal barrier function and reversed gut microbiota dysbiosis by reducing the level of circulating endotoxin and proinflammatory cytokines (Jiang et al, 2020 ).…”
Section: The Gut Microbiota and Alcohol-induced Acute Liver Injurymentioning
confidence: 99%